2016
DOI: 10.1177/0018720816644364
|View full text |Cite
|
Sign up to set email alerts
|

Human–Robot Interaction

Abstract: Objective:The current status of human-robot interaction (HRI) is reviewed, and key current research challenges for the human factors community are described.Background: Robots have evolved from continuous human-controlled master-slave servomechanisms for handling nuclear waste to a broad range of robots incorporating artificial intelligence for many applications and under human supervisory control.Methods: This mini-review describes HRI developments in four application areas and what are the challenges for hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 509 publications
(134 citation statements)
references
References 22 publications
0
96
0
2
Order By: Relevance
“…Despite impressive advances in the recent decade, current robotics engineering is still distant from developing 297 robotic systems able to assist human individudals socially, especially during postural activities and balance 298 exercises (Sheridan, 2016). In the both rIPT conditions of the current study, the dynamics of the robotic system 299 were not independent but in one way or another a direct consequence of CR's movements.…”
Section: Robotic Control 205mentioning
confidence: 79%
“…Despite impressive advances in the recent decade, current robotics engineering is still distant from developing 297 robotic systems able to assist human individudals socially, especially during postural activities and balance 298 exercises (Sheridan, 2016). In the both rIPT conditions of the current study, the dynamics of the robotic system 299 were not independent but in one way or another a direct consequence of CR's movements.…”
Section: Robotic Control 205mentioning
confidence: 79%
“…RIFs on Trust were modeled, accordingly; namely Automation Etiquette and AW. Sheridan and Parasuraman (2005) identify influences affecting performance in human machine interaction. One influence highlighted and hence integrated in the present model (as a node) is Automation Etiquette.…”
Section: Bayesian Belief Networkmentioning
confidence: 99%
“…For instance, it has been outlined as a fundamental need for robots that consciously navigate in the presence of humans, in order to develop a "human-aware" navigation strategy [1]. Additionally, fueled by recently proposed specifications (ISO/TS 15066:2016-Robots and robotic devices-Collaborative robots), it will likely be essential in the near future for the realization of the "intimate collaboration" or the "close proximity interaction" paradigms described by [2,3], respectively. In particular, studies have shown recently that human motion prediction technologies have the potential to improve the efficiency of the team and the perception of safety and comfort by the user in different settings in which persons and robots share the same physical workspace [4,5].…”
Section: Introductionmentioning
confidence: 99%